Incarceration of transplanted kidney through incisional hernia. Issue 6 (16th June 2021) - Nawabi, Atta; Marlor, Derek; Camarata, Christopher; King, Clay D; Nawabi, Perwaiz
Abstract: Transplanted allograft kidney herniation through an incisional hernia resulting in incarceration is a rare condition with only one other similar case reported in the literature. The primary imaging modalities used to diagnose kidney herniation are graft ultrasound, abdominal computed tomography and abdominal magnetic resonance imaging [Sugi et al. (Imaging of renal transplant complications throughout the life of the allograft: comprehensive multimodality review. Radiographics 2019;39 :1327-1355)]. Treatment should be based on patient's symptoms. This case report highlights the initial presentation of hematuria in a 57-year-old male that eventually led to the diagnosis of a right-sided incarcerated grafted kidney through an incisional hernia. Subsequently, the patient underwent transplant nephrectomy.